Systematic Literature Review: Arsitektur Berkelanjutan pada Kenyamanan Penghuni Aspek Pencahayaan Alami di Perumahan Bersubsidi Tamara Alfa Sinergia - Ridhani, Muhammad; Rahman, Akbar; Febrita, Yuswinda (Nusantara Journal of Science and Technology, 2025)
Natural daylighting is an essential element in creating healthy and functional housing environments. Poor daylighting quality may result in uneven light distribution between spaces, excessively dark areas, or excessive glare in certain rooms. Subsidized housing developments generally apply uniform building orientations and elongated spatial layouts, which often limit the effective distribution of natural light. As a result, central spaces such as family rooms frequently experience insufficient daylight due to obstruction by surrounding rooms. These conditions indicate the need for an in-depth evaluation of natural daylighting to understand its impact on occupants’ visual comfort. This study aims to synthesize findings from various scientific literature on natural daylighting in tropical residential buildings and to compare these findings with the design conditions of Tamara Alfa Sinergia Subsidized Housing in Banjarbaru. The research employs a Systematic Literature Review (SLR) approach combined with field observations to assess natural daylighting performance in subsidized housing, specifically at the Tamara Alfa Sinergia residential complex. The results indicate that the application of natural daylighting in the studied housing meets the basic principles of sustainable architecture, particularly through the use of openings on the front and rear façades, building orientation aligned with the site layout, and compact spatial configurations that allow daylight penetration into main living spaces. However, further improvements are recommended through the optimization of openings, spatial layouts, and passive design strategies to enhance occupants’ visual comfort while supporting long-term energy efficiency.